Milk Consumptionand Supply of Ulaanbaatar City - Bazarragchaa, Ichinkhorloo; Luvsandorj, Nyambat; Qian, Lu (Asian Journal of Agriculture and Rural Development, 2015)
Ulaanbaatar city (UB) is not only capital and the largest city with continuously growing populations in Mongolia. The people, who must consume milk at highest amounts, are those living in urban areas, especially UB city. Current level of domestic liquid milk production is not met consumption of capital city and other biggest cities. The objective of this study is to analyze market equilibrium of liquid milk (Estimations were relied on the information regarding cow milk, which has the highest yield than milk from other species of five types of livestock) market of UB city, and determine level of milk supply. Market theory, including demand and supply analyses were applied using regression analyses to estimate functional forms and other required statistical- econometrical indicators. Secondary data gathered from National Statistical Office (2004-2014) and methodology for converting adult equivalence methodology cited from methodological guidance. According to the study results, main finding was comparatively bigger deficit of liquid milk market of UB warn weak position of liquid milk security level (794.4 t <237.8 t). Therefore, support of domestic liquid milk producers should be desirable to improve market condition as well as national food security issue. It is clear that in the future more advanced development of intensified dairy farms and supports of their activities are essential in order to meet the demands.